Has fiscal expansion inflated house prices in China? Evidence from an estimated DSGE model - Chunping Liu; Zhirong Ou (Cardiff University, Cardiff Business School, 2019)
A canonical DSGE model for housing, extended to embrace government spending and governmentinvestment, is estimated on Chinese data to evaluate the impact of Öscal policy on house prices. Govern-ment spending substitutes for housing; a rise in government spending lowers house prices, but its impactis weak. Government investment generates a wealth eect, causing housing demand, and therefore prices,to rise; its variation had a substantial impact on the boom-bust cycles of house prices in the past decade.Both government spending and government investment are eective instruments for manipulating output.However, their dierent impacts on house prices would recommend policies to count more on spendingif Öscal expansion is not to sacriÖce the stability of house prices.
Keywords: E62; R31; 330; fiscal policy; housing price; China; DSGE model